Removal of naproxen from wastewater using chitosan-aerogel-activated carbon biocomposites Theory, equilibrium, kinetics, thermodynamics, and process optimization - Ozcan, Nazli (Water environment research : a research publication of the Water Environment Federation, 2022)
© 2022 Water Environment Federation.